Characterization of Magnetic Properties of the Coastal Sand Deposits in South Beach of Manokwari, West Papua - Sangaji Hasmi Maharani Ipa; Siti Hadjar Kubangun; Satria Bijaksana; Darharta Dahrin; Innaa Uswatun Hasanah (Journal of Natural Sciences and Mathematics Research, 2018)
Coastal sand deposits containing iron particles (magnetic) can be regarded as iron sand and it generally has color from gray to shiny black yet while it is mixed with other minerals, the mineral will have a certain color combination. Coastal sand in the South of Manokwari Regency, West Papua especially in Wosi Beach, Arfai Beach, and Maruni Beach has a different color of the grain according to the source rocks and the sedimentation process. To characterize the magnetic properties of the three coastal sand deposits, several experimentations were done through measurements of the density, magnetic degree, magnetic susceptibility, and also SEM (Scanning Electron Microscopy) and EDS (Energy Dispersive X–Ray Spectroscopy) tests. The coastal sand deposition has a density ranging from 2.50–5.00 g cm-3 with the magnetic degree between 0.28–36.29 % and its magnetic susceptibility ranged 80.9×10-8 – 7447.7×10-8 m3 kg-1. The coastal sand from Arfai Beach has a magnetic susceptibility between the coastal sand from Wosi and Maruni Beach with the highest value reaching 5135.4 × 10-8 m3 kg-1. This is also supported by SEM and EDS data. The percentage of iron element mass (Fe) of the identified magnetic grain distribution in Wosi Beach sand is 6.71–33.90%, Arfai Beach sand is 11.35 – 38.45% and Maruni beach sand is 15.84–44.41%. ©2018 JNSMR UIN Walisongo. All rights reserved.